1993
DOI: 10.1247/csf.18.1
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Expression of Neural Cell Adhesion Molecule Isoforms During Chicken Embryonic Myogenesis.

Abstract: Keywords: neural cell adhesion molecule/muscle-specific domain/myogenesis/antipeptide antibody ABSTRUCT. The neural cell adhesion molecule, NCAM, is known to be expressed in chicken muscle as at least three principal molecular forms (molecular masses of 155 kDa, 145 kDa, and 120 kDa). They are generated from a single gene by alternative splicing. To distinguish these molecular species and to investigate their expressions in muscle differentiation during chicken embryonic development, we prepared antipeptide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
6
11
0
Order By: Relevance
“…Thus, each splice variant of NCAM that differs in its attachment to the plasma membrane can also be expressed either containing or lacking the MSD region. This interpretation of the identity of NCAM polypeptides is in agreement with the studies of Yoshimi et al (1993) on the 155-and 145-kD forms of NCAM expressed during skeletal muscle development.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, each splice variant of NCAM that differs in its attachment to the plasma membrane can also be expressed either containing or lacking the MSD region. This interpretation of the identity of NCAM polypeptides is in agreement with the studies of Yoshimi et al (1993) on the 155-and 145-kD forms of NCAM expressed during skeletal muscle development.…”
Section: Discussionsupporting
confidence: 90%
“…As reported by Yoshimi et al (1993) we found the 155-kD isoform to be transiently expressed, being high between St 32-38 and then being down regulated along with the 145-kD isoform later in development. The tightly and differentially regulated expression of all three isoforms during in vivo myogenesis suggests that they may be playing distinct roles.…”
Section: Regulation Of Ncam Isoforms During Primary and Secondary Myosupporting
confidence: 85%
“…Some molecular weight variations in these reported forms could also be due to variations in glycosylation other than sialylation or to differing phosphorylation states (Sorkin et al, 1984;Rutishauser et al, 1988;Hoffman et al, 1982). However Yoshimi et al (1993) have reported that in chick thigh muscle from the same embryonic stages that we have studied, the 155-kD isoform has the muscle-specific domain (MSD) insert , whereas the 145-kD isoform does not. They also reported that the MSD domain is present in the 130-kD isoform.…”
Section: Regulation Of Ncam Isoforms During Primary and Secondary Myomentioning
confidence: 90%
“…2B, second row). The blot of sialidase-treated NCAM shows switching in the synthesis of NCAM from the TM form to the GPI ϩ MSD form as differentiation progresses, consistent with the developmental change of NCAM isoforms in chick embryonic muscle (25). Lectin blots using PNA, which is specific for O-linked Gal␤1-3GalNAc, showed that the GPI ϩ MSD isoform is O-glycosylated during days 2-8 (Fig.…”
Section: Ncam-msd and Polysialic Acid Are Sequentially Expressed On Tsupporting
confidence: 72%